2019
DOI: 10.1590/0004-282x20190050
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of transcranial doppler ultrasound for cerebral small vessel disease in elderly patients

Abstract: Objective: To investigate the predictive value of transcranial Doppler (TCD) ultrasound for cerebral small vessel disease in elderly patients. Methods: Transcranial Doppler ultrasound and magnetic resonance imaging (MRI) were performed on 184 elderly patients with cerebral small vessel disease. The relationship of clinical characteristics and TCD ultrasound parameters with severe white matter lesions (WMLs) in MRI were investigated by univariate analysis and multivariate analysis. Results: The univariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…14,37,38 Microangiopathy, including impairment of cerebral vessels, is a frequent complication of DM. 7,8,39 Lee et al 39 showed that PI in the MCA was significantly higher in DM patients with complications than in those without complications and in healthy controls, and is closely correlated with the duration of DM. Hemodynamic changes are observed not only in type 2, but also in type 1 DM, and are also enhanced in the long-term diabetes group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,37,38 Microangiopathy, including impairment of cerebral vessels, is a frequent complication of DM. 7,8,39 Lee et al 39 showed that PI in the MCA was significantly higher in DM patients with complications than in those without complications and in healthy controls, and is closely correlated with the duration of DM. Hemodynamic changes are observed not only in type 2, but also in type 1 DM, and are also enhanced in the long-term diabetes group.…”
Section: Discussionmentioning
confidence: 99%
“…Small vessel disease (SVD) belongs to the relatively frequent disorders influencing the RI a PI in the cerebral arteries. 8 SVD is a disorder of the brain's small perforating arterioles, capillaries, and probably venules that causes various brain lesions detected using brain magnetic resonance or computed tomography. 9,10 Typical lesions are white matter hyperintensities of presumed vascular origin, lacunes, microbleeds, superficial siderosis, perivascular spaces, and microinfarcts.…”
mentioning
confidence: 99%
“…Though no direct anatomical information can be obtained, TCD permits for the evaluation of mean flow velocity (MFV) changes in the major cerebral arteries after a vasodilative stimulus and it provides complementary information of the brain hemodynamics (Ringelstein et al, 1988;Ebrahim et al, 2019;Burley et al, 2021a). The results of the TCD examination (MFV and pulsatility index) and the ventilation tests correlate with those obtained by other methods, and the value of TCD in the evaluation of CVR impairment, e.g., in the asymptomatic or symptomatic individuals with the brain white matter lesions (WMLs) has been established (Maeda et al, 1993;Marcos et al, 1997;Ghorbani et al, 2015;Fu et al, 2019). The assessment of CVR can be achieved with the bilateral recording of MFV in the middle cerebral artery (MCA) with acceptable reproducibility and inter-rater reliability using carbogen inhalation (McDonnell et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of Arquivos de Neuro-Psiquiatria, Fu et al 23 report on an evaluation of 184 elderly patients with cerebral small vessel disease as shown by transcranial Doppler and MRI 23 . They observed that the elevated pulsatility index obtained in the middle cerebral artery was significantly correlated with severe WMHs, using the Fazekas scale.…”
mentioning
confidence: 99%
“…In addition, the pulsatility index described in most scientific papers should be cited as the Gosling pulsatility index 25 . Another important consideration is related to the ethnic group in the study by Fu et al 23 . Cerebral blood flow velocities and pulsatility index patterns may be affected by ethnicity not only during the examination, with respect to the temporal window, but also by the predominance of specific vascular diseases.…”
mentioning
confidence: 99%